The gloss to decision of the Supreme Court of 30 May 2017 in the case no. II PK 125/16 – approving gloss - Pieczonka, Piotr (Studia Iuridica Toruniensia, 2018)
The gloss concerns the Supreme Court’s decision of 30 May 2017 in the case no. II PK 125/16, in which the Supreme Court considered that the binding force in the scope resulting from Art. 365 of the Civil Procedure Code does not mean binding the court with the findings contained in the justification of another ruling. The issues raised in the above Supreme Court’s ruling and in the gloss refer to the controversy in jurisprudence and doctrine related to the binding force of the ruling, i.e. the answer to the question whether the binding force of a ruling (court’s decision or nonprocedural order) in a civil case is used only for the decision and whether or not the binding force of the court’s decision extends to matters beyond the sentence of the judgment, including the findings and assessments regarding the legal relationship underlying the request for which it was adopted. The gloss brings closer the view of the Supreme Court in the commented case, as well as the position of the doctrine and indicates the arguments for adopting a position that supports the thesis that under Art. 365 of the Civil Procedure Code, the binding force of the ruling refers only to its sentence and does not include its justification.